PENGEMBANGAN MEDIA POHON NUMERASI MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH 11-20 KELAS I SD NEGERI 37 CAKRANEGARA - Ilahiat, Yayang Waridat; Dewi, Nurul Kemala; Rosyidah, Awal Nur Kholifatur (Jurnal Ilmiah PENDAS: Primary Educational Journal, 2023)
The aims of this study were (1) to explain the process of making mathematical numeration tree media for addition and subtraction of whole numbers 11-20, (2) to find out the feasibility and practicality of math numeration tree media for adding and subtracting whole numbers for class I SD. The type of research used is Research and Development (R&D) using the ASSURE development model. The research instrument used a validation questionnaire sheet for material experts, media experts, and questionnaires for teacher and student responses. The results showed that the criteria were feasible with a percentage of 76.36% from material experts and 85.71% from media experts. While the results of the teacher and student response questionnaires show very practical criteria with a percentage of 90% from the teacher response questionnaire and 97% from the student response questionnaire. So, it can be stated that the numeration tree media for adding and subtracting whole numbers 11-20 is feasible from the feasibility and practical aspects to be used as a learning medium for class I students at SD Negeri 37 Cakranegara.